Uji sifat fisik dan kimia bioetanol dari jagung (Zea mays L) - Tira, H.S.; Mara, M.; Zulfitri, Z.; Mirmanto, M. (Dinamika Teknik Mesin, 2018)
The aim of this research is to know the physical characteristics and chemical contents of corn bioethanol (Zea Mays L.). The bioethanol is produced by distillation process through variations in fermentation duration. The bioethanol produced then was tested in order to measure the physical characteristics and sulphur content. The measured physical and chemical characteristics of bioethanol were density, kinematic viscosity, flash and fire point and sulphur content.The results showed that the physical characteristic value and sulphur content of the bioethanol had close values compared to those of the standart. They were found in fermentation with duration of 70 hours under second distillation process. However a further research is still be required to obtain a suitable characteristic for transpostation purpose.